2011
DOI: 10.3354/ame01533
|View full text |Cite
|
Sign up to set email alerts
|

Feeding, growth and metabolism of the marine heterotrophic dinoflagellate Gyrodinium dominans

Abstract: Rates of grazing, growth, and respiration were studied in the heterotrophic dinoflagellate Gyrodinium dominans experiencing a single pulse of prey. Additionally, rates of grazing and growth were compared to those of G. dominans growing with constant concentrations of prey. The maximal specific growth rates of G. dominans with a single pulse of prey were similar to those observed when G. dominans was acclimated to constant levels of prey. Thus, our results support the hypothesis that the growth of G. dominans r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
2
6
1
Order By: Relevance
“…As reported by Schmoker et al (2011), we also observed a drop in ingestion rates of GYR at high prey concentrations. This may indicate that this species does not thrive well in eutrophic conditions, in contrast to OXY, which keeps feeding at maximum rates even at very high prey concentrations.…”
Section: Feeding Responses To Food Quantitysupporting
confidence: 89%
See 2 more Smart Citations
“…As reported by Schmoker et al (2011), we also observed a drop in ingestion rates of GYR at high prey concentrations. This may indicate that this species does not thrive well in eutrophic conditions, in contrast to OXY, which keeps feeding at maximum rates even at very high prey concentrations.…”
Section: Feeding Responses To Food Quantitysupporting
confidence: 89%
“…The rates found in this study fall within those reported by Goldman et al (1989), Roberts et al (2011), and Nakamura et al (1995) for OXY feeding on a variety of prey, and for overall heterotrophic dinoflagellates summarized by Jeong et al (2010). However, they are lower than the specific values presented by Schmoker et al (2011) and the per cell rates shown in Hantzsche & Boersma (2010) for GYR and OXY, respectively, feeding on RHO. The discrepancies between these specific works and our results will be discussed later.…”
Section: Feeding Responses To Food Quantitysupporting
confidence: 86%
See 1 more Smart Citation
“…During the spring and summer, when the gyrodinoid morphotype was predominantly chlorophyll-containing, it may have been feeding on small autotrophs. Certain species of gyrodinoids, such as Gyrodinium dominans, have been found to respond quickly to increases in cryptophytes (Schmoker et al 2011), which can be important at that time of year.…”
Section: Discussionmentioning
confidence: 99%
“…; Schmoker et al. ), there are, to our knowledge, no reports of heterotrophic dinoflagellate growth rates after starvation. The focus of this study was to compare the functional and numerical responses of three cosmopolitan heterotrophic dinoflagellates ( O. marina , Gyrodinium spirale and G. dominans ) in response to different food conditions (continuously‐fed vs. starved) and over different time scales (hours vs. days).…”
mentioning
confidence: 92%